Socio-Demographic and Clinical Characteristics of Iraqi Crystal Meth Users - Hussein Al-Ka'aby; Marwa Jameel; Adnan Yaseen; Ahmed Al-Imam; Nesif Al-Hemiary (Iraqi Journal of Pharmaceutical Sciences, 2025)
Methamphetamine, known as crystal meth, is a potent psychostimulant frequently abused for recreational purposes. Despite its prevalence, methamphetamine abuse in Iraq remains insufficiently understood. The study aims to examine the characteristics of methamphetamine users in Iraq, encompassing socio-demographic factors, economic aspects, clinical presentations, co-occurring psychiatric conditions, and physical comorbidities. Patients were recruited from Baghdad Medical City and Ibn-Rushd Teaching Hospital. Comprehensive data were gathered on patient demographics, frequency of methamphetamine use, clinical manifestations, attempts at substance abstinence, associated psychosomatic disturbances, and potential triggering events leading to stimulant use disorder, among other variables. Our study involved 165 patients with crystal methamphetamine addiction, comprising males (92.1%) and females (7.9%). Although males were slightly older than their female counterparts (26.7 versus 25.5, p-value=0.696), this difference was not statistically significant. Most methamphetamine users were married (48.5%), had barely completed primary school education (51.5%), resided in urban areas (87.3%), and engaged in freelance work (72.1%). Most patients reported daily substance use over an extended period (1-5 years), primarily through inhalation. Users frequently experienced auditory and visual hallucinations, with persecutory delusions being prevalent. On the contrary, fewer individuals exhibited delusions of infidelity. Poly-substance abuse was prevalent, with alcohol being the most commonly abused substance. Notably, many users spent approximately $200 monthly on acquiring crystal meth. Our research highlights multifaceted challenges faced by methamphetamine users, particularly young males, encompassing socio-economic difficulties, limited education, unstable employment, urban living, and existing marital commitments. Successful recovery hinges on addressing these issues and providing affordable treatment, with medically supervised detoxification essential for managing withdrawal manifestations.